2021
DOI: 10.3390/f12010097
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Dynamics of Vegetation Diversity and Aboveground Biomass of Picea abies (L.) H. Karst. Forests after Heavy Windstorm Disturbance

Abstract: Although forest disturbances have become more frequent and severe due to ongoing climate change, our understanding of post-disturbance development of vegetation and tree–herb layer interactions remains limited. An extreme windstorm, which occurred on 19 November 2004, destroyed Picea abies (L.) H. Karst dominated forests in the High Tatra Mts. Here, we studied short-term changes in diversity, species composition, and aboveground biomass of trees and herb layer vegetation, including mutual relationships that el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, relationships between forest overstorey and understorey can be also competitive. The recent evidence suggested that forest structures typical fora higher belowground and aboveground competition can lead to a decrease in the understorey diversity and also biomass production troughout forest succession or gap dynamics (Mölder et al 2014(Mölder et al , 2008Ujházy et al 2017;Slezák & Hrivnák 2019;Máliš 2021b).…”
Section: Consequences Of Forest Management On the Production And Biod...mentioning
confidence: 99%
“…However, relationships between forest overstorey and understorey can be also competitive. The recent evidence suggested that forest structures typical fora higher belowground and aboveground competition can lead to a decrease in the understorey diversity and also biomass production troughout forest succession or gap dynamics (Mölder et al 2014(Mölder et al , 2008Ujházy et al 2017;Slezák & Hrivnák 2019;Máliš 2021b).…”
Section: Consequences Of Forest Management On the Production And Biod...mentioning
confidence: 99%
“…The transects are 4 m wide and 300 m long. Detailed data from both transects have already been analyzed in our previous works, which thoroughly describe their stand properties [13,23].…”
Section: Research Site and Transectsmentioning
confidence: 99%
“…We studied the effects of forest successional stages and management intensity on the abundance and species richness [4]. Similar studies have been conducted in the territory of the Slovak Republic with a focus on damage to soil and remaining forest stands by machines, evaluation of abiotic controls of wind disturbance using the generalized additive model [5][6][7], with a focus on spruce forests [8,9], and an analysis of the qualitative features of beech and oak trunks as a determinant of quality assessment [10].…”
Section: Introductionmentioning
confidence: 99%